(untitled) (Western European Journal of Medicine and Medical Science, 2025)
Rosa sumneviczii Korotkova is a rare and understudied wild rose species endemic to the Western Pamir-Alay region of Uzbekistan. Initially described in 1948, it is taxonomically distinct from closely related taxa such as Rosa kokanica, based on morphological characteristics including spine shape, stem bark color, and sepal orientation. The species has an extremely limited known distribution, restricted to its type locality near Ak-Kishlak in the Kashkadarya Region. This study integrates morphological evaluation, spatial conservation metrics, and climate-based species distribution modeling (SDM) to assess its current and future conservation status. Six georeferenced records from iNaturalist in 2024 were used to calculate an extent of occurrence (EOO) of 0.073 km² and an area of occupancy (AOO) of 722 km², qualifying the species as Critically Endangered under IUCN Criterion B1 and Vulnerable under Criterion B2, respectively. No known populations fall within protected areas. Using MaxEnt and climate projections for 2070 under RCP 8.5, suitable future habitats were identified not only at the current locality but also in adjacent parts of Tajikistan and Afghanistan. These findings highlight both the conservation urgency and potential transboundary conservation value of this narrowly endemic species. Immediate conservation actions, including in situ habitat protection and targeted field surveys in climatically suitable areas, are essential for the survival of R. sumneviczii.